Causative factors on the dynamics of economic viability on acceptance of sustainable agriculture practices among Malaysian contract farmers - Alby, Jeffrey Lawrence D'Silva; Abu Samah, Bahaman; Mohamed Shaffril, Hayrol Azril; Azman, Azmariana (WFL Publisher, 2012)
The purpose of this study was to identify the level of the economic dimension of sustainable agriculture practices among contract farmers in Malaysia and the factors that predict the variance in this economic dimension. Survey research methodology using the multi-stage sampling method was used to collect data from 319 contract farmers across four zones in Malaysia. The dependent variable was the economic dimension of sustainable agriculture practices while the predictor variables were selected socio-demographic factors, attitude, knowledge, support and belief. It was identified through the multiple regression method that the belief and attitude factors were able to explain about 17.6% of the variance of the economic dimension of sustainable agriculture practices. The study recommends that more factors need to be studies to further understand the complexities associated with farmers’ acceptance on the economic dimension of the sustainable agriculture practices.